Assessment of knowledge about body postural defects among parents - Karolina Klimkiewicz-Wszelaki; Remigiusz Sokołowski; Paulina Kasperska; Eliza Oleksy; Anna Ziółkowska; Wojciech Stemplowski; Ewelina Nesteruk; Cyryl Kwiatkowski; Kornelia Kędziora-Kornatowska; Walery Zukow (Kazimierz Wielki University, 2019)
Introduction: Postural defects became in recent decades significant problem, both medical and social. Many examinations show that faulty posture affect about 60-80 per cent of children. The rapid development of technology has led to limiting of physical activity which manifests itself by massive occurrence of faulty posture. Therefore it is extremely important to increase the parents knowledge and awareness of the prevention and correction of faulty posture as well as benefit from physical activity. Aim: The aim of the present study was estimation parents knowledge about faulty posture and verification who knows more - parents who have children with correct posture or these who have children with postural defects as well as parents who encourage children to exercise or these who don't do this. Materials and methods: A survey was conducted in a group of 60 parents. First group: 30 parents of children attending The Postural Defect Clinic, second group: 30 parents of children attending School Complex No. 8 in Bydgoszcz. The original questionnaire was used for the study. Questionnaire to the estimation of parents knowledge consisted of 19 questions: metric questions and knowledge test. The results were analyzed statistically (p